Diagnostic accuracy of glycogen phosphorylase BB for myocardial infarction: A systematic review and meta‐analysis. Issue 5 (24th March 2022) - Ghimire, Anup; Giri, Subarna; Khanal, Niharika; Rayamajhi, Shivani; Thapa, Anjila; Bist, Anil; Devkota, Surya
Abstract: Purpose: We tried to investigate the diagnostic accuracy of glycogen phosphorylase BB as a cardiac marker for myocardial infarction. Methods: We searched through different electronic databases (PubMed, Google‐scholar, Embase, and Cochrane Library) to locate relevant articles. Studies, with sufficient data to reconstruct a 2 × 2 contingency table, met our inclusion criteria were included. Three reviewers independently screened the articles. Discrepancies were resolved by other reviewers. Unpublished data were requested from the authors of the study via email. Subsequently, data extraction was done using a standardized form and quality assessment of studies using the QUADAS‐2 tool. Meta‐analysis was done using a bivariate model using R software. Results: Fourteen studies were selected for the final evaluation, which yielded the summary points: pooled sensitivity 87.77% (77.52%–93.72%, I 2 = 86%), pooled specificity 88.45% (75.59%–94.99%, I 2 = 88%), pooled DOR 49.37(14.53–167.72, I 2 = 89%), and AUC of SROC was 0.923. The lambda value of the HSROC curve was 3.670. The Fagan plot showed that GPBB increases the pretest probability of myocardial infarction from 46% to 81% when positive, and it lowers the same probability to 12% when negative. Conclusion: With these results, we can conclude that GPBB has modest accuracy in screening myocardial infarction, but the limitations of the study warrant further high‐quality studies to confirm its usefulness in predicting myocardial infarction (MI). Abstract : Our study is a systematic review and meta‐analysis done to evaluate GPBB as a potential biomarker for the prompt diagnosis of MI. 14 studies were selected for evaluation after a thorough screening. Our results (AUC = 0.923, DOR = 49.37) have led to the conclusion that GPBB serves as a moderately accurate biomarker for the early diagnosis of MI and could revolutionize the treatment protocol currently set for MI. We do recognize that our paper comes with its set of limitation therefore, further studies on the topic is still needed.